A literature review of the neurobiological and behavioral substrates of food addiction: Food Addiction - Reisi, Fatemeh; Ghaderi, Amir (International Journal of Medical Toxicology and Forensic Medicine, 2026)
Background: Food addiction (FA) is a multifaceted behavioral disorder involving an uncontrollable craving for high-calorie, palatable foods. FA plays an important role in threatening public health. The purpose of this literature review is to systematically examine the multifaceted nature of FA by elucidating the neurobiological, psychological, and environmental factors involved. Methods: This literature review adhered to PRISMA guidelines and searched international databases, including PubMed, Scopus, ScienceDirect, IranDoc, Civilica, and SID, from 2014 to July 2025. Fourteen high-quality studies that met the inclusion criteria were identified using relevant keywords. Results: Three main drivers of key pathophysiological mechanisms in FA have been identified: hormonal dysregulation, impaired inhibitory control, and reward system dysregulation. Two emerging research areas have also been identified: genetic and epigenetic factors and dysregulation of the gut-brain axis. Factors influencing the development of FA include individual, sociocultural, neurobiological, and cognitive factors. Conclusion: Managing FA requires an interdisciplinary approach targeting its behavioral and biological components. Effective prevention is a public health imperative that depends on a three-pronged strategy of public education, improved food policies, and healthier environments. This integrated approach, which spans subject treatment and population-level intervention, is essential to mitigating the incidence and societal burden of the disorder.